2004
DOI: 10.1084/jem.20040643
|View full text |Cite|
|
Sign up to set email alerts
|

CCR7 Signals Are Essential for Cortex–Medulla Migration of Developing Thymocytes

Abstract: Upon TCR-mediated positive selection, developing thymocytes relocate within the thymus from the cortex to the medulla for further differentiation and selection. However, it is unknown how this cortex–medulla migration of thymocytes is controlled and how it controls T cell development. Here we show that in mice deficient for CCR7 or its ligands mature single-positive thymocytes are arrested in the cortex and do not accumulate in the medulla. These mutant mice are defective in forming the medullary region of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
401
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(424 citation statements)
references
References 41 publications
21
401
1
1
Order By: Relevance
“…37,38 Consistent with this, cortical DP thymocytes show increased CCR7 expression, 38,39 and CCR7 ligands (CCL21 and CCL19) are predominantly expressed in thymic medulla area, especially mTECs. 38,40 Defective cortex-to-medulla migration has been found in mice deficient for CCR7 or CCR7 ligands, 38 whereas the forced expression of CCR7 on premature thymocytes results in the relocation of DP thymocytes to the medulla. 37 Furthermore, impaired central tolerance was found by our group and others in CCR7-and CCR7L-deficient mice.…”
Section: Central Tolerancesupporting
confidence: 58%
“…37,38 Consistent with this, cortical DP thymocytes show increased CCR7 expression, 38,39 and CCR7 ligands (CCL21 and CCL19) are predominantly expressed in thymic medulla area, especially mTECs. 38,40 Defective cortex-to-medulla migration has been found in mice deficient for CCR7 or CCR7 ligands, 38 whereas the forced expression of CCR7 on premature thymocytes results in the relocation of DP thymocytes to the medulla. 37 Furthermore, impaired central tolerance was found by our group and others in CCR7-and CCR7L-deficient mice.…”
Section: Central Tolerancesupporting
confidence: 58%
“…3, D and E). plt mice have significantly reduced SLC expression and no ELC expression (32,33) and significant arrest of cortex-to-medulla migration of SP cells was reported in plt mice due to lack of SLC/ELC thymic expression (29). Similar to that in plt thymi, in the medulla of Ltbr Ϫ/Ϫ thymi, the CD8SP cell numbers were found also significantly reduced compared with that in WT thymi (Fig.…”
Section: Lt␤r Deficiency Leads To Preserved Ectopic Mova Expression Bmentioning
confidence: 52%
“…These two chemokines are produced predominantly in the medulla of thymus. Their receptor, CCR7, is expressed on semimature thymocytes, and has been recently shown to be important for the thymocytes migration from cortex to medulla (29,30). By quantitative real-time PCR, we found both SLC and ELC were significantly reduced in the Ltbr Ϫ/Ϫ thymi compared with those in WT mice (Fig.…”
Section: Lt␤r Deficiency Leads To Preserved Ectopic Mova Expression Bmentioning
confidence: 68%
See 1 more Smart Citation
“…SP thymocytes migrate from the cortex into the medulla of the thymus. CCR7 signal is required for SP thymocyte migration into the thymic medullary region as in CCR7 or CCR7 ligand deficient mice, mature SP thymocytes accumulate in the cortex instead of medulla [137]. Recently, we have shown that anti-apoptotic protein c-FLIP is required for SP thymocyte maturation by providing protection against apoptosis [138].…”
Section: Sp Thymocytes and Negative Selectionmentioning
confidence: 97%